Pemberian Silase Campuran Rumput Lapangan – Legume Clitoria Ternatea dan Konsentrat sebagai Pakan Komplit terhadap Kadar Hemoglobin, Kolesterol dan Trigliserida Darah Sapi Bali Jantan Penggemukan Pola Peternak: The Effect of Feeding Mixed Silage of Field Grass – Legume Clitoria Ternatea and Concentrate as Complete Feed on Hemoglobin, Cholesterol and Triglyceride Blood Levels of Bali Male Fatting Breeding Patterns - Laos, Wildy Sesicho Carlile; Rosnah, Upik Syamsia; Amalo, Daud (Universitas Nusa Cendana, 2024)
The purpose of this study was to determine the levels of hemoglobin, cholesterol, and bloodtriglycerides in the fattening pattern of male bali cattle breeders which will be affected by mixedfield grass - legume clitoria ternatea and concentrate as complete feed. The livestock used in thisstudy were 8 feeder cattle with an average body weight of 112.88 kg and an age of 1 to 1.5 years.The Latin Square Design, with 4 treatments and 4 replication periods, was the researchmethodology used. In this study there were three different treatments: P0: farmer pattern feed(control), P1: farmer pattern (60%) + Grass-Legume Silage (30%) + Concentrate (10%), P2:farmer pattern (50% ) + Grass Silage - Legumes (40%), and P3: Cropping Patterns (40%) + Grass-Legume Silage. The levels of hemoglobin, cholesterol, and triglycerides in the blood are the testvariables of the study. Analysis of variance was used to calculate the data (ANOVA). g/dlhemoglobin and mg/dl cholesterol. Based on the results of the analysis, the therapy did not have asignificant impact (P>0.05) on the blood metabolites of Bali cattle fed to gain weight. Based on theresults of this study, it can be concluded that the silage of a mixture of field grass-legume Clitoriaternatea and concentrate can be utilized up to 50% because it gets the same results on hemoglobin,cholesterol, and triglyceride levels. bali cattle fattening. Tujuan dari penelitian ini adalah untuk mengetahui kadar hemoglobin, kolesterol, dan trigliseridadarah pada pola penggemukan peternak sapi bali jantan akan dipengaruhi oleh silase mixed fieldgrass - legum clitoria ternatea dan konsentrat sebagai pakan lengkap. Ternak yang digunakandalam penelitian ini adalah 8 ekor sapi bakalan dengan bobot badan rata-rata 112,88 kg dan umur1 sampai 1,5 tahun. Rancangan Bujur Sangkar Latin, dengan 4 perlakuan dan 4 periode ulangan,merupakan metodologi penelitian yang digunakan. Pada penelitian ini terdapat tiga perlakuan yangberbeda: P0: pakan pola petani (kontrol), P1: pola petani (60%) + Silase Rumput-Legum (30%) +Konsentrat (10%), P2: pola petani (50% ) + Silase Rumput - Legum (40%), dan P3: Pola Tanam(40%) + Grass-Legume Silage. Kadar hemoglobin, kolesterol, dan trigliserida dalam darah adalahvariabel uji studi. Analisis varians digunakan untuk menghitung data (ANOVA). g/dl hemoglobindan mg/dl kolesterol. Berdasarkan hasil analisis, terapi tidak memberikan dampak yang berarti(P>0,05) terhadap metabolit darah sapi bali yang diberi pakan untuk menambah berat badan.Berdasarkan hasil penelitian ini dapat disimpulkan bahwa silase campuran rumput lapangan-legumClitoria ternatea dan konsentrat dapat dimanfaatkan hingga 50% karena mendapat hasil yangsama terhadap kadar hemoglobin, kolesterol, dan trigliserida.penggemukan sapi bali.